You are Here: Home >< Maths

# Simple question: Why does -x-3/x+3 =-1? watch

1. Explain how it works? I keep thinking it's -2 because -x/x = -1 and -3/3 = -1?
2. (Original post by Airess3)
Explain how it works? I keep thinking it's -2 because -x/x = -1 and -3/3 = -1?
-x-3=-1 times x+3.
3. (Original post by Airess3)
Explain how it works? I keep thinking it's -2 because -x/x = -1 and -3/3 = -1?
It is not true that .
4. -x-3 = -1(x+3)

so -1 = -x-3/(x+3)
5. (Original post by Airess3)
Explain how it works? I keep thinking it's -2 because -x/x = -1 and -3/3 = -1?
Factor out the negative -x-3 = -(x+3)

-(x+3)/(x+3)
6. Trolling or serious?
7. (Original post by Airess3)
Explain how it works? I keep thinking it's -2 because -x/x = -1 and -3/3 = -1?
I thought you were an undergraduate - this is GCSE stuff!

-x-3 = -(x+3) so the result follows immediately

I'm assuming you mean since it's not clear from your layout.
8. (Original post by langlitz)
Factor out the negative -x-3 = -(x+3)

-(x+3)/(x+3)
Thanks. I see now.

TSR Support Team

We have a brilliant team of more than 60 Support Team members looking after discussions on The Student Room, helping to make it a fun, safe and useful place to hang out.

This forum is supported by:
Updated: December 4, 2014
Today on TSR

### University open days

• University of Roehampton
Sat, 17 Nov '18
• Edge Hill University
Faculty of Health and Social Care Undergraduate
Sat, 17 Nov '18
• Bournemouth University
Sat, 17 Nov '18
Poll
Useful resources

### Maths Forum posting guidelines

Not sure where to post? Read the updated guidelines here

### How to use LaTex

Writing equations the easy way

### Study habits of A* students

Top tips from students who have already aced their exams